THE MANAGEMENT OF PATIENTS PRESENTED WITH BLACK STONE POISONING: AN EXPERIENCE OF A TERTIARY CARE HOSPITAL - Haqdad, Mehwish; Qureshi, Sameer; Ahmed, Anam (Pakistan Armed Forces Medical Journal, 2021)
Abstract